Analisa Infrastruktur Desa Sukaci-Baros Dengan Metode Critical Path Method (CPM) - Nalhadi, Ahmad; Suntana, Nana (Jurnal Sistem dan Manajemen Industri, 2017)
CV. ABP a construction company worked in infrastructure building development for private and goverment. Now CV. ABP is handling infrastructure development project of the acropolitan area (Right Payment) Sukaci - Baros Village. This project has been late for 19 days from the dead line 126 days. Therefore the cost is getting higher. It happened because bad management is the problem source. Restoring the project time need to be focused on the cost and the due date based on the schedule. Scheduling evaluation using Critical Path Method (CPM) and Crashing to find optimal results using Critical Path Method (CPM) can be found the critical paths activity, there are ground digging , bopflang installation, stone installation, agregrate B agrgregation , aggregate A flatting, rigit bavement work, and refining, when the time suppression obtained optimal time results from 126 days to 92 days. It taken an alternative to the addition of working hours with duration 92 day after the crashing. Using two alternatives, additional working hours and the addition of workforce, obtaining the difference of extra hours of work cost Rp 80.128.125 and labourcost increase Rp 55.260 from the regular cost.